Numerical Simulation of Solvent Injection for Late-stage Steamflood - Budi, Iwan Setya (Penerbitan Universitas Trisakti, 2025)
This paper evaluates the solvent injection process to recover remaining oil during late-stage of a steamflood using numerical simulation. After Steam Break through, a steamflood recovery will enter a late period identified by increasing Steam-Oil Ratio (SOR). It reduces the economics since steam is an intensive energy process aiming to recover oil quickly, much quicker than chemical EOR. Solvent is expected to substitute a large amount of steam injection and able to lower heavy oil viscosity. In oilfield worldwide, solvent is often used as an alternative for SAGD where well configuration is uniquely arranged using a pair of horizontal wells as injector and producer. However, instead of horizontal well pair as in SAGD, this study examines common pattern (inverted 9 spot) in steamflood project which mainly utilizes vertical wells for both injector and producer. Using thermal methods, the fluid production favorably tends to be higher, but heat loss associated from surface line down to subsurface can hurt the economics. Three scenarios are developed and studies resulting that oil recoveries achieved are not signifacntly lower however at the same time requires much lower energies (and cost) for solvent injection.